Health leaders’ perspectives and attitudes on medical assistance in dying and its legalization: a qualitative study - Amanda Yee; Eryn Tong; Rinat Nissim; Camilla Zimmermann; Sara Allin; Jennifer L. Gibson; Madeline Li; Gary Rodin; Gilla K. Shapiro (BMC Medical Ethics)
Abstract Background Medical Assistance in Dying (MAiD) has transformed health policy and practice on death and dying. However, there has been limited research on what shaped its emergence in Canada and the beliefs and views of health leaders who hold positions of influence in the healthcare system and can guide policy and practice. The objective of this study was to examine health leaders’ perspectives on the factors that led to the emergence of MAiD and explore their attitudes about the legalization of MAiD. Methods In this qualitative study, we conducted online semi-structured interviews with health leaders from April 2021 to January 2022. Purposive and snowball sampling techniques were used to recruit health leaders who have expertise and engagement with the delivery of MAiD or palliative and end-of-life care, and who hold positions of leadership relevant to MAiD in their respective organisations. Inductive thematic analysis was used to analyze the transcribed interviews. Results Thirty-six health leaders were interviewed. Participants identified six factors that they believed to have led to the introduction of MAiD in Canada: public advocacy and influence; judicial system and notable MAiD legal cases; political ideology and landscape; policy diffusion; healthcare system emphasis on a patient-centred care approach; and changes in societal and cultural values. Participants expressed wide-ranging attitudes on the legalization of MAiD. Some described overall agreement with the introduction of MAiD, while still raising concerns regarding vulnerability. Others held neutral attitudes and indicated that their attitudes changed on a case-by-case basis. Participants described four factors that they considered to have had influence on their attitudes: personal illness experiences; professional experiences and identity; moral and religious beliefs; and, the valence of patient autonomy and quality of life. Conclusions This study highlights the wide-ranging and complex attitudes health leaders may hold towards MAiD and identifies the convergence of multiple factors that may have contributed to the legalization of MAiD in Canada. Understanding health leaders’ attitudes and perspectives on the legalization of MAiD may inform stakeholders in other countries who are considering the legalization of assisted dying.